Effects of Alpha-Ketoglutarate Supplementation on Growth Performance, Diarrhea Incidence, Plasma Amino Acid, and Nutrient Digestibility in Weaned Piglets - Weiyan Sun; Ruyi Han; Hongbo Xi; Wenning Chen; Yanpin Li; Qingchao Zhou; Xilong Li; Kaikun Huang; Valentino Bontempo; Xu Gu; Xianren Jiang (Animals, 2025)
Alpha-ketoglutaric acid (AKG) is a key intermediate in the tricarboxylic acid cycle and plays a crucial role in energy production and amino acid metabolism. This study aimed to evaluate the effects of AKG on growth performance, nutrient digestibility, plasma biochemical parameters, and plasma amino acid profiles in weaned piglets. A total of 72 weaned piglets with an average weight of 7.33 kg (±0.50 kg) and an average age of 28 (±2 days) were randomly assigned to 3 dietary treatments with 6 replicates per group in a 42-day trial. The treatments included a basal diet (CT), a basal diet with 500 g/t AKG (AKG1), and a basal diet with 1000 g/t AKG (AKG2). Blood samples were collected on days 14 and 42, and fecal samples were collected on day 42. The results showed that diets including 500 g/t and 1000 g/t AKG significantly reduced diarrhea incidence in piglets compared to the CT group (p < 0.01). Moreover, diets including 1000 g/t AKG enhanced fecal dry matter digestibility, plasma albumin (ALB), and glucose (GLU) concentrations on day 42 compared to the AKG1 group (p < 0.05). In conclusion, diets including AKG reduced diarrhea incidence in weaned piglets, potentially through improved nutrient digestibility and enhanced systemic health. The 1000 g/t level exhibited greater beneficial effects than 500 g/t.